2008
DOI: 10.1074/jbc.m708347200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p97-dependent Protein Degradation by Eeyarestatin I

Abstract: Elimination of misfolded proteins from the endoplasmic reticulum (ER) by ER-associated degradation involves substrate retrotranslocation from the ER lumen into the cytosol for degradation by the proteasome. For many substrates, retrotranslocation requires the action of ubiquitinating enzymes, which polyubiquitinate substrates emerging from the ER lumen, and of the p97-Ufd1-Npl4 ATPase complex, which hydrolyzes ATP to dislocate polyubiquitinated substrates into the cytosol. Polypeptides extracted by p97 are eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
210
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(222 citation statements)
references
References 61 publications
10
210
1
Order By: Relevance
“…Thus, we sought to address the issue using a chemical inhibitor of ERAD. Eer1 interacts with p97 to regulate ERAD negatively, resulting in the accumulation of polyubiquitinated intermediates (43,44). Our results, using KB cells as a model system, failed to confirm an essential role for p97, although our studies were limited in scope and now await an expanded investigation of PE-toxin interactions with the ERAD pathway.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Thus, we sought to address the issue using a chemical inhibitor of ERAD. Eer1 interacts with p97 to regulate ERAD negatively, resulting in the accumulation of polyubiquitinated intermediates (43,44). Our results, using KB cells as a model system, failed to confirm an essential role for p97, although our studies were limited in scope and now await an expanded investigation of PE-toxin interactions with the ERAD pathway.…”
Section: Discussioncontrasting
confidence: 45%
“…If ERAD were necessary, one could expect hits near the top of the mitigator list, but no hits related to the ERAD pathway were noted in top mitigators (or sensitizers). Because the participation of ERAD could not be assessed definitively from our siRNA data, we addressed the issue using the chemical inhibitor, Eeyarestatin 1 (Eer1), which interacts with p97 to regulate ERAD negatively, resulting in the accumulation of polyubiquitinated intermediates (43,44). It has also been suggested that Eer1 inhibits Sec61-mediated protein translocation, because it targets a component of the Sec61 complex that forms the membrane pore of the ER translocon (45).…”
Section: Resultsmentioning
confidence: 99%
“…2A). Further validation of these results was obtained by treating cells with Eeyarestatin (Eer)I, an irreversible inhibitor of VCP (25,26). Similar to treatment with DBeQ or knockdown of VCP, treatment with 10 μM EerI before infection potently inhibited neutralization of AdV by mAb 9C12 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Protein bands were quantified using the Odyssey 2.1. Astrocytoma or 293T cells stably expressing FLAG-US2 were generated using the pLNCX2-based retroviral system as described previously (29). 293T cell stably expressing YFP tagged T-cell receptor ␣ chain and astrocytoma cells stably expressing US11 were described previously (28,29).…”
Section: Methodsmentioning
confidence: 99%